EPIDEMIOLOGICAL STUDY OF SCHISTOSOMIASIS AND ITS ASSOCIATED RISK FACTORS AMONG PRIMARY SCHOOL PUPILS IN JIBIA LOCAL GOVERNMENT AREA OF KATSINA STATE, NIGERIA - Usman, Abbas; Eberemu, N. C.; Orpin, J. B. (FUDMA JOURNAL OF SCIENCES, 2025)
Schistosomiasis is a chronic disease that is linked to poverty. Contact with fresh water infested with parasitic blood fluke (Schistosomes spp.) larvae (cercariae) can result in infection. The study aimed to determine the prevalence of Schistosomiasis among Jibia Local Government Area primary school pupils. Questions about risk factors, human water contact behaviour, and sociodemographic data were distributed to 300 randomly chosen pupils. Both stool and urine samples were examined under a microscope using sedimentation techniques, and the Medi-Test Combi-9 test strip was used for chemical analysis. S. intercalatum was present in just 1 out of 300 cases (0.3%) while S. haematobium in 83 cases (27.7%), haematuria in 85 cases (28.3%), and proteinuria in 33. Yet, Muhammad Rabiu Model Primary School has a much higher prevalence of S. hematobium 37 (44.6%) and just one S. intercalatum than Tukare Primary School, which has 20 (20.1%) S. hematobium and zero S. intercalatum, respectively, when compared to other schools. The school's closeness to a water body (Jibia Dam) may be the cause of this. Infection rates do not significantly differ by age group (P = <0.001) or gender (P = 5.621). However, compared to pupils without formal education, children whose parents are uneducated have an Odd Ratio (OR) of 36.7 higher infection rates (P = 0.01). In conclusion, the study area is endemic for S. haematobium, and in addition to personal hygiene, molecular detection of S. intercalatum is recommended.